THE PROBLEM OF THE POLITICAL STATUS OF TIBET ACCORDING TO THE SIMLA CONVENTION OF 1914: THEORETICAL AND HISTORICAL ASPECTS - A. Klinov (Гуманитарные и юридические исследования)
The relevance of the topic lies in the strategic significance of Tibet both in the first half of the twentieth century and now. Historical analysis of international competition on the issue of the status of Tibet allows us to draw important theoretical conclusions about the typology of international relations and forms of statehood in the East. The novelty of the work is that the author introduces new sources in foreign languages into scientific circulation. Changes in the status of Tibet in the context of great power competition and differences in the typology of forms of political and territorial structure in Chinese and Western political traditions are revealed. The author determined that the Simla Convention of 1914 preserved the status of Outer Tibet as part of the state territory of China and Chinese suzerainty over Outer Tibet. The Simla Convention recognized Outer Tibet as an Autonomous state with political autonomy rights. However, this international act limited China's position in Tibet. China was granted the right to observe the state of Affairs in Outer Tibet, nothing more. British India found more opportunities in Outer Tibet than China. Western countries and China perceived the meaning of the Simla Convention in a negative way, in accordance with their political and legal traditions. Therefore, China refused to ratify the Simla Convention. After the signing of the Simla Convention, Tibet tried to secede from China and obtain official recognition of its sovereignty. The author gives an interpretation of the types of territorial and political structure, revealing the differences between unitary, Federal, Confederation, monarchical Union and forms of autonomy in unitary States. The similarity of vassal States in the Chinese tradition and Autonomous entities in the Western sense is noted. From China's point of view, Tibet was part of the geopolitical belt of vassal political entities that did not have independence. China wanted the United Kingdom and the United States to revoke Tibet's political autonomy and allow China to establish military and administrative control over Tibet. These interests of China were not supported by the British Empire and the United States.